Teaching Strategies and their Implication in the Significant Learning of the Concept of Derivative in Engineering Students - Medina Cepeda, Niorka Margarita; Delgado Fernández, José Ramón (Rastros Rostros, 2017)
Introduction: his article intends to determine the teaching strategies used to promote the significant learning of the concept of derivative in engineering students. For this, it was theoretically based on Ausubel, Díaz and Hernández, among others. Materials and methods: It was framed by a quantitative methodology, being a descriptive research with a cross-sectional, field design. A population census of seven professors teaching Calculus I from the School of Engineering at the Universidad del Zulia was considered. The data collection technique was the surveyand a questionnaire of 42 Likert-type items was designed as an instrument, with high reliability of 0.899 according to the Cronbach’s alpha method. For data analysis, descriptive statistics by means were used. Results: It was obtained as a result that professors sometimes use strategies to promote significant learning. Conclusions: Given the results obtained, it is concluded that didactic strategies should be organized to optimize teaching performance and reinforce their teaching tools, refresh their knowledge, keep up with itc advances, and turn them into efficient facilitators that ensure the expected significant learning in the field of study.
Keywords: significant learning; derivative; teaching performance; teaching strategies